2019
DOI: 10.1159/000500138
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for New-Onset Diabetes Mellitus after Heart Transplantation in Chinese Patients: A Single Center Experience

Abstract: Background: New-onset diabetes after transplantation ­(NODAT) is a frequent complication after heart transplantation (HT) and is associated with graft loss and patient survival. Objectives: The aim of this study was to identify the incidence and associated factors contributing to NODAT in Chinese heart transplant recipients. Methods: Adult patients without diabetes mellitus before HT were enrolled in this study. NODAT was diagnosed according to the criteria recommended by the American Diabetes Association. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…A large number of studies have reported that age is a risk factor for PTDM, which selected the age of 45 years as the cutoff to study the relationship between age and PTDM. Studies have reported that kidney transplant patients aged ≥ 45 years have a higher risk of developing PTDM than patients aged < 45 years in Chinese heart transplant ( Zhang et al, 2019 ). In addition, age ≥ 45 years increases PTDM risk 2.2 times when compared to individuals of 18–44 years old in American kidney transplant recipients ( Cosio et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have reported that age is a risk factor for PTDM, which selected the age of 45 years as the cutoff to study the relationship between age and PTDM. Studies have reported that kidney transplant patients aged ≥ 45 years have a higher risk of developing PTDM than patients aged < 45 years in Chinese heart transplant ( Zhang et al, 2019 ). In addition, age ≥ 45 years increases PTDM risk 2.2 times when compared to individuals of 18–44 years old in American kidney transplant recipients ( Cosio et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…All enrolled patients received triple immunosuppressive regimens according to the local protocol, consisting of tacrolimus (Prograf; Astellas Pharma, Dublin, Ireland), MMF (MMF; CellCept; Roche, Shanghai, China), and glucocorticoid (Prednisone; Huazhong Pharmaceutical, Xiangyang, Hubei, China). 14 Patients received a dense sampling with 10 points, before medication, and 0.5, 1, 1.5, 2, 4, 6, 8, 10, and 12 hours after dosing. Blood samples were collected in ethylenediaminetetraacetic acid tubes.…”
Section: Samplesmentioning
confidence: 99%
“…1,13 The incidence of PTDM in HTRs ranges from 15.7% to 40.0%. 13,2124 The registry of the ISHLT reported an incidence of PTDM of 21.0% at 1 year and 34.5% at 5 years after HT. 25 Ethnicity may play a role in the development of PTDM; non-white race has been identified as an independent risk factor for PTDM in HTRs.…”
Section: Discussionmentioning
confidence: 99%